Inescapable entrapments? : the civil-military decision paths to Uruzgan and Helmand - Mantas, Mirjam Grandia (Leiden University Pess, 2021)
Military involvement in foreign policy decision-making, and its role as a driving force in that process, has long been anathema to both academic and practitioner circles. Without wanting to pursue the quest for principles or ultimate predictions this study looks specifically into the role of the military in foreign policy decision-making. It does so by carefully reconstructing and comparing the sequential series of decisions of a group of British and Dutch senior civil and military decision-makers which have led to the deployment of their militaries into to Afghan provinces of Helmand and Uruz.